Heavy Metals Pollution Assessment of the Soil in the Northern Site of East Baghdad Oil Field, Iraq - S. Mohammed , Mena; J. Abdullah, Enaam (Iraqi Journal of Science, 2023)
Twenty four soil samples were collected from different sites in north sector of East Baghdad oil field, Iraq , and analyzed to assess the impact of urbanization and industrialization essential pollution. The soil samples were analyzed for heavy metals (As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn) by using inductively coupled plasma–mass spectrometry (ICP-MS). Mean concentration of heavy metals in soil samples follows this pattern: Zn > Ni > Cr > Cu >Pb > As> Cd> Hg. The results show significant variations (lower and higher) in the concentrations of heavy metals compared with local and world studies, this variation is attributed to the natural anthropogenic sources. The pollution of studied soil was assessed using many soil pollution indices; Contamination Factor (CF) shows for Zn , Ni , Cr , Cu ,Pb , As, Cd and Hg were distributed between low to moderate contamination, while the Degree of Contamination (Cd )values ranges from moderate degree of contamination very high degree of contamination indicating serious anthropogenic pollution, the Pollution Load Index (PLI) values were ˃1 confirming there is considerable contamination ,and the Ecological Risk Factor (Eri) values were classified as low to high potential ecological risk. These results indicate the significant need for the development of pollution prevention and reduction strategies to reduce heavy metal pollution for regions undergoing fast industrialization and urbanization.